A new Traffic Separation Mechanism (TSm) in Wireless 802.11e Networks: A simulation study - Ricardo Moraes (2006)
Wireless Local Area Networks (WLAN) has attracted significant interest to support real-timecommunication. The most promising solution was recently published as IEEE 802.11e, which provide trafficdifferentiation. However, that solution still has an inadequate behavior to support real-time applications. Inthis paper, we propose a new traffic separation mechanism for IEEE 802.11e networks. Such TrafficSeparation Mechanism (TSm) allows the coexistence of CSMA standard stations with modified (real-time)stations in the same network domain. We investigate the performance of TSm mechanism through computersimulations. We show the efectiveness of such scheme when the real-time traffic is kept at reduced loads orwhen we have only one producer real-time traffic station.